Social Media and The Boycott Behavior of Indonesian Investors due to The Israeli-Palestinian Conflict: The Role of Hatred as a Mediator - Kusuma, Septian Yudha; Wahyuni, Mirasanti; Makom, Maharani Rona; Widiarto, Ardian; Martia, Dina Yeni (LPPM ISNJ Bengkalis, 2025)
Objective: The ongoing boycott movement of products affiliated with Israel has caused a decline in sales and could potentially lower stock prices. This study focuses on the perspective of investors in the behavior of boycotting Israeli-affiliated companies, with antecedents of the role of social media and hatred. Methods: This study used random and simple snowball sampling techniques and collected 358 respondents. Respondents received the accessible questionnaires via social media and direct delivery. The statistical procedures applied for hypothesis testing include validity and reliability testing, discriminant validity, multicollinearity, heterotrait-monotrait ratio (HTMT), and direct and mediation hypothesis testing. Results: The study shows that hatred significantly arises from social media exposure; social media and hatred influence stock boycott behavior. In contrast, hatred is important in mediating the influence of social media and investor behavior. Recommendation: The study's results provide empirical evidence and contributions regarding the factors influencing investors' boycott behavior and enrich the literature on the antecedents and consequences of intentions in investment boycotts.